(untitled) (Research, Society and Development, 2021)
This is a discussion about the interfaces between artifact, culture and local development, considering the artisanal processes of felting sheep wool produced in the Serra da Mantiqueira. It is justified by the absence of research focused on different socio-technical, socio-cultural and economic approaches to the production/use of wool. The goal is to understand the set of knowledge used in the making of felting to subsequently subsidize alternative practices for the use of this fiber in the region, especially for the manufacture of handicraft products. The methodological proposal is structured in interviews with craftsman, field observation and use of images of handmade products taken from social networks and craftsman’ websites and other images sent by them for this article. It is believed that there may be an expansion in the use of this material, from the universe of data used, given the versatility of felted wool and the diversity of possibilities for using the fibers. The research points to an inclination of alternative use of wool, as opposed to the classification of the industry, in terms of local development, to create a network of wool production in order to avoid purchasing the material in other regions.